Ten years of coverage of trophy hunting in UK newspapers - Yeomans, Nikita; Hare, Darragh; Dröge, Egil; Hart, Adam G. (Frontiers in Conservation Science, 2022)
Hunting is an increasingly contentious topic. Trophy hunting, whereby people hunt individual animals with desirable characteristics in order to keep body parts (e.g. horns, heads, hides, antlers) as mementos, is especially contested. Political pressure, often in the form of trophy import bans, is being applied in multiple nations, and campaigns to ban trophy hunting, or trophy imports, attract considerable media attention. However, trophy hunting often has conservation value, acting to protect habitat and provide income for local communities. Assuming that media coverage can influence public and political opinion, negative or simplistic media coverage of trophy hunting has the potential to cause adverse outcomes for conservation and local communities. Here, we analyse coverage of trophy hunting from July 2010 - June 2020 (five years before and five years after the death of Cecil the Lion) in the most popular UK media outlets (624 articles in total), assessing the overall sentiment of each article, and the species and countries covered. Ninety percent of all coverage occurred after the death of Cecil the lion, marking this event as a watershed moment in UK mainstream media depiction of trophy hunting. The overall sentiment of articles was largely against trophy hunting (63.1%), and this was more pronounced in tabloids (84.2%) than broadsheets (42.2%). Pro-trophy hunting articles were very uncommon overall (3.5%). Articles that described the complexity of trophy hunting decreased following Cecil and were most common in pre-Cecil broadsheets (35.7%, dropping to 30.6%) and rarest in post-Cecil tabloids (3.1%). Articles focussed mainly on charismatic but rarely hunted species including lion, elephant and rhino, with commonly hunted species (such as impala or Cape buffalo) only rarely being mentioned. When countries were mentioned, southern African nations predominated, with four nations (Zimbabwe, South Africa, Namibia and Botswana) being named in 68% of qualifying articles. We conclude that simplistic media depiction of trophy hunting has the potential to cause negative outcomes for conservation through its impact on public perception and political opinion.